Advances in management accounting - Malina, Mary A., (Advances in Management Accounting,, 2017)
This volume is a publication of quality appliedresearch in management accounting. The volumespurpose is to publish thought-provoking articles that advance knowledge in themanagement accounting discipline and are of interest to both academics andpractitioners. The book seeksthoughtful, well-developed articles on a variety of current topics inmanagement accounting, broadly defined. All research methods including surveyresearch, field tests, corporate case studies, experiments, meta-analyses, andmodeling are welcome. Some speculativearticles, research notes, critiques, and survey pieces will be included whereappropriate. Articles may range from purely empirical to purely theoretical,from practice-based applications to speculation on the development of newtechniques and frameworks. Empiricalarticles must present sound research designs and well-explained execution. Theoretical arguments must present reasonableassumptions and logical development of ideas. All articles should include well-defined problems, concisepresentations, and succinct conclusions that follow logically from the data.This volume intends to provide authors with timely reviews clearly indicatingthe acceptance status of the manuscript. The results of initial reviews normally will be reported to authorswithin eight weeks from the date the manuscript is received. The author will be expected to work with theEditor, who will act as a liaison between the author and the reviewers toresolve areas of concern. To ensure publication,it is the author's responsibility to make necessary revisions in a timely andsatisfactory manner.